Ritual Myths in Traditional Dance Performances of Aceh, Java, Bali, Kalimantan, Sulawesi, and Papua - Gunawan Wiradharma; Sri Sediyaningsih; Pamela Mikaresti (Dinasti International Journal of Education Management And Social Science, 2025)
The insertion of myth into ritual events and supernatural powers in a dance performance certainly has a greater purpose. Something sacred and considered to have supernatural powers certainly has a value that cannot be grasped by common sense, so the mysteriousness of myths is still difficult to consider as truth. In general, this research aims to comprehensively examine the myths that develop in dance performance rituals, especially in the lives of the people of Aceh, Java, Bali, Kalimantan, Sulawesi, and Papua. This research method is qualitative research carried out by describing facts. The results of this research show that the background to the emergence of myths in ritual dance in Aceh, Java, Bali, Kalimantan, Sulawesi, and Papua is based on folklore that developed in these areas. Apart from that, it was also found that the main motives for creating myths were monotheism and ecological motifs. The bond and awareness between humans, the universe, and God create a balanced relationship so that a safe, secure, and protected situation is created. In this case, it can be seen that myths are not just reports of events that previously occurred, but myths provide direction to human behavior and are a guide in determining human wisdom.